Knowledge-Based Economy: A Proposal of Different Points of View and Economic Theories Reconciliation Basing on Management Methods Evolution - Riccardo VALENTE (Communications of International Proceedings, 2025)
The text discusses, first of all, the strong knowledge-based economy concept linkage with Neoclassical theory. It presents then alternative interpretations emerging out of Piketty (2014) work and Post-Keynesian theory. Considering data about income distribution, economic growth, capital accumulation and capital to income ratio evolution through the whole 20th and 21st century, it is then argued that their explanation requires integrating the demand-based Post-Keynesian focus on income inequalities increases negative effects on physical capital accumulation and economic growth, on one hand, and human capital and technical change role analysis derived from supply-side Neoclassical endogenous growth theory, on the other hand. Those data, moreover, do not fit traditional 19th century Neoclassical income distribution theory, based on productive factors relative scarcity and diminishing returns concepts. They support, instead, the older Classical socio-political and historical events-based determination of distribution, negating as well both Neoclassical and Keynesian limitation of the income distribution theory to profits and salaries determination, when high income inequalities and economic instability and growth stagnation show up. After considering higher value of housing to income and increased role of intangible assets in US and European firms stock market value determination currently registered, finally, an integration of Neoclassical, Classical, Keynesian and Post-Keynesian theory basing on management methods historical evolution, which led, since the end of industrial revolution, to the substitution of rigid physical capital intensive production methods with more flexible human capital intensive ones, is proposed, stressing how it can help explaining most of the phenomena currently observed in developed economies and worldwide.
Keywords: Knowledge-based economy; economic growth; income distribution; capital accumulation